2022
DOI: 10.1159/000524303
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Regucalcin Suppresses the Growth, Migration, Invasion, and Adhesion of Metastatic Human Prostate Cancer Cells

Abstract: Regucalcin plays a multifunctional role in the regulation of cellular function including metabolism, signaling process and transcriptional activity in maintaining cell homeostasis. Downregulated expression or activity of regucalcin contributes to the development of malignancies in various types of human cancer. Survival of cancer patients, including metastatic prostate cancer, is prolonged with high expression of regucalcin in the tumor tissues. Furthermore, we elucidate whether extracellular regucalcin conque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, extracellular regucalcin has been found to have suppressive effects on the growth, colony formation, migration, invasion, and adhesion of metastatic human prostate cancer PC-3 and DU-145 cells in vitro, as reported in [182]. The suppressive effects of extracellular regucalcin may result from a decrease in levels of multiple signaling proteins, such as Ras, phosphatidylinositol-3 kinase, MAP kinase, mTOR, RSK-2, caveolin-1, and integrin β1, in PC-3 cells [182]. This study demonstrated in vitro inhibition of metastatic activity by extracellular regucalcin.…”
Section: The Suppressive Role Of Extracellular Regucalcin In the Canc...mentioning
confidence: 52%
See 2 more Smart Citations
“…Interestingly, extracellular regucalcin has been found to have suppressive effects on the growth, colony formation, migration, invasion, and adhesion of metastatic human prostate cancer PC-3 and DU-145 cells in vitro, as reported in [182]. The suppressive effects of extracellular regucalcin may result from a decrease in levels of multiple signaling proteins, such as Ras, phosphatidylinositol-3 kinase, MAP kinase, mTOR, RSK-2, caveolin-1, and integrin β1, in PC-3 cells [182]. This study demonstrated in vitro inhibition of metastatic activity by extracellular regucalcin.…”
Section: The Suppressive Role Of Extracellular Regucalcin In the Canc...mentioning
confidence: 52%
“…A greater expression of regucalcin in tumor tissues extends the survival of patients with different cancer types. Recent studies have shown that extracellular regucalcin, found in the extracellular fluids of various tissues, suppresses the growth of several types of human cancer cells, such as HepG2 liver cancer cells [180], MiaPaCa-2 pancreatic cancer cells [179], MDA-MB-231 breast cancer cells [181], PC-3 prostate cancer cells [182], SK-OV-3 ovarian cancer cells [177], and Saos-2 osteosarcoma cells [161]. Extracellular regucalcin contributes to suppressing cancer cell growth in the cancer microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation